Design of a Transfer Chute for Multiple Operating Conditions - Gutierrez-Silva, A (American Society of Mechanical Engineers, 2014)
The kinematic and dynamic flow behavior of granular material on a transfer chute whose main feature is that it can adapt to different operating conditions while maintaining its configuration is studied. As a result, a geometry is obtained that can fulfill some design criteria such as minimum wear of the linings; easy change of the geometry for different configurations, minimize the probability of plugging; fast return to normal operating conditions after a jam; prevent spillage loss of material; and minimum dimensions. The design is obtained by a simulation based on the discrete element method (DEM), considering the mechanical properties of all the materials involved, with a particle size distribution in line with normal operating conditions, incorporating the distribution of the material s size and moisture related to friction, cohesion and adhesion phenomena. The LIGGGHTS open source program is used to calculate the movement of the material, and the ParaView program to process the results. Copyright © 2014 by ASME.